2016
DOI: 10.2166/wst.2016.579
|View full text |Cite
|
Sign up to set email alerts
|

Passive neutralization of acid mine drainage using basic oxygen furnace slag as neutralization material: experimental and modelling

Abstract: This study investigated passive neutralization of acid mine drainage using basic oxygen furnace slag as neutralization material over 90 days, with monitoring of the parameters' quality and assessment of their removal kinetics. The quality was observed to significantly improve over time with most parameters removed from the influent during the first 10 days. In this regard, removal of acidity, Fe(II), Mn, Co, Ni and Zn was characterized by fast kinetics while removal kinetics for Mg and SO were observed to proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Passive treatment systems involve a combination of alkaline reagents and utilization of natural biochemical processes in artiicially constructed wetlands, ponds, and alkaline-generating drains [25][26][27]. Innovative acid mine drainage treatment using unconventional alkaline agents such as slag has been evaluated [28,29]. The steel slags on contact with the AMD increased the pH to circumneutral levels and reduced the levels of most major inorganic contaminants such as Al, Fe, Ti, Ni, Be, and Cu.…”
Section: Acid Mine Drainage Treatment Using Coal Ly Ashmentioning
confidence: 99%
“…Passive treatment systems involve a combination of alkaline reagents and utilization of natural biochemical processes in artiicially constructed wetlands, ponds, and alkaline-generating drains [25][26][27]. Innovative acid mine drainage treatment using unconventional alkaline agents such as slag has been evaluated [28,29]. The steel slags on contact with the AMD increased the pH to circumneutral levels and reduced the levels of most major inorganic contaminants such as Al, Fe, Ti, Ni, Be, and Cu.…”
Section: Acid Mine Drainage Treatment Using Coal Ly Ashmentioning
confidence: 99%
“…Passive AMD neutralization was achieved using basic oxygen furnace slag as neutralization material over 90 days and metal removal kinetics was assessed (Zvimba et al, 2017). The study provided insights into better understanding of the potential use of slags and their limitations for AMD treatment.…”
Section: Impacts Of Detrital Nano-and Micro-scale Particlesmentioning
confidence: 99%
“…Nowadays the most common utilization patterns include road project construction, cement production, plant recycling and et al (Saha et al 2019, Yang et al 2021. Although many efforts were made to increase the steel slag recycling ratio in the construction materials, however, the performance of the produced construction materials was frequently substandard (Zvimba et al 2017), because the free CaO, MgO and other easily hydrated components in steel slag could deteriorate the cement stability associated with the volume stability of the products (Zhang et al 2020, Yu et al 2015. It was reported that the acceptable contents of f-CaO and MgO should be lower than 7% and 4% when the steel slags were used in unbound and bitumen bound layers (Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The alkalinity concentration was close to stable after 60 min. For the mentioned L/S ratio (1:100), the stable alkalinity was in a range of 100-110 mg/L and the corresponding pH of the ltrate was 10.5.Calcium containing components in BOF slags were mainly originated from ux materials during the steel making process, like lime, limestone (Zvimba et al 2017…”
mentioning
confidence: 99%